A survey on nonstrategic models of opinion dynamics - Michel Grabisch; Agnieszka Rusinowska (Games, 2020)
The paper presents a survey on selected models of opinion dynamics. Both discrete (more precisely, binary) opinion models as well as continuous opinion models are discussed. We focus on frameworks that assume non-Bayesian updating of opinions. In the survey, a special attention is paid to modeling nonconformity (in particular, anticonformity) behavior. For the case of opinions represented by a binary variable, we recall the threshold model, the voter and q-voter models, the majority rule model, and the aggregation framework. For the case of continuous opinions, we present the DeGroot model and some of its variations, time-varying models, and bounded confidence models.
Keywords: 330; binary opinion; continuous opinion; non-Bayesian updating; nonconformity; opinion dynamics